The Influence of Service Quality, Discipline, and Workload on Employe Performance at the Peudada Sub-District Office - Khairul Ambia; Sri Balkis; M. Hulaimi; Muhammad Nazar; Muhammad Fajri (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the effect of work discipline and work This study aims to determine the simultaneous influence of service quality, discipline and workload on employee performance at the Peudada Sub-district Office. The research location is at the Peudada Sub-district Office. The population of this study was 40 civil servants. The sample of this study was 40 civil servants. The method used is a quantitative method with a multiple linear regression model, to analyze the influence of the independent variable (free) on the dependent variable (bound) using SPSS. Based on the results of the study, it is known that the results of the partial test with a value of t count> t table (4,077> 2,028) a significant probability of 0.025 <0.05, indicating that the Service Quality variable affects employee performance at the Peudada Sub-district Office. The results of the partial test with a value of t count >t table (2,145> 2,028) a significant probability of 0.045 <0.05, indicating that the Discipline variable affects employee performance at the Peudada Sub-district Office. The partial test result of t count < t table (-2,919 < 2,028) significant probability of 0.026 < 0.05, indicates that the Workload variable affects employee performance at the Peudada Sub-district Office. The partial test result of F count > F table (9,041 > 2,87) with a significance of F of 0.000 with a probability of < 0.05. So it can be concluded that H0 is rejected H3 is accepted. This means that the variables of Service Quality, Discipline and Workload together (simultaneously) have a significant influence on employee performance variables at the Peudada Sub-district Office.